Evaluation of school media resource libraries in Singapore government primary schools. - Soraya Rosyanne Abdul Rahim. (2008)
This research examines whether the Media Resource Library (MRL) programme is heading in the same direction as the school or cluster mission. It also examines the impact of the MRL initiatives on the school population with regard to its attempt to attain success in achieving stated programme goals and objectives. This study investigates both students' and teachers' needs that can be subsequently translated into programme policies, school policies, procedures and activities. It identifies the strengths and accomplishments of the MRL programme and further identifies the challenges faced that require improvement.